Synthesis of Various Heterocycles from 3-(Naphthylene-3-yl)-1H-pyrazol-4-carbaldehyde - SHELKE, S.N.; DALVI, N.R.; GILL, C.H.; KARALE, B.K. (Asian Journal of Chemistry, 2010)
Various substituted o-hydroxy acetophenone (1), on condensation with 3-(naphthylene-3-yl)-1H-pyrazol-4-carbaldehyde (2) yields 1-(2-hydroxyphenyl)-3-(3-naphthalen-3-yl)-1-(phenyl-1Hpyrazol- 4-yl)prop-2-en-1-one (3), which on treatment with hydrazine and catalytic amount of iodine in presence DMSO gives pyrazoline (4) and chromone derivatives (5), respectively. Compound 5 reacts with hydrazine in ethanol to afford the pyrazole 6. The constitution of these compounds was elucidated on the basis of spectral studies.